RELATIONSHIP BETWEEN KNOWLEDGE AND ATTITUDES AND TUBERCULOSIS PREVENTION AMONG PULMONARY TUBERCULOSIS PATIENTS - Mubin Barid (Journal of Innovation Research and Knowledge, 2026)
Abstract: Background: Tuberculosis (TB) remains a major public health problem worldwide and continues to contribute significantly to morbidity and mortality, particularly in developing countries. Patients’ knowledge and attitudes play an important role in influencing preventive behaviors and reducing disease transmission. This study aimed to determine the relationship between knowledge and attitudes of pulmonary tuberculosis patients and their tuberculosis prevention efforts in the working area of Singkawang Utara 1 Public Health Center. Methods: This quantitative study employed an analytical cross-sectional design. The study population consisted of all registered pulmonary tuberculosis patients in the working area of Singkawang Utara 1 Public Health Center. A total sampling technique was used, involving 32 respondents. Data were collected using structured questionnaires assessing knowledge, attitudes, and tuberculosis prevention practices. Statistical analysis was conducted using the Chi-square test with a significance level of 0.05. Results: Most respondents had poor knowledge (56.3%), negative attitudes (75.0%), and inadequate tuberculosis prevention practices (53.1%). Statistical analysis revealed a significant relationship between knowledge and tuberculosis prevention efforts (p = 0.000). In addition, a significant relationship was found between attitudes and tuberculosis prevention efforts (p = 0.028). Conclusion: Knowledge and attitudes are significantly associated with tuberculosis prevention efforts among pulmonary tuberculosis patients. Improving patient education and promoting positive attitudes toward disease prevention may enhance preventive behaviors and contribute to reducing tuberculosis transmission in the community.